Determination of Taxpayer Compliance with Risk Preferences as a Moderation Variable - Ni Putu Tiara Maharani Krisna Putri; Ni Nyoman Ayu Suryandari; Ni Putu Lisa Ernawatiningsih (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2025)
Indonesia's national development can be advanced by optimizing domestic sources of funds, particularly through effective taxation. This research aims to analyze the influencing factors of taxpayers on taxpayer compliance, with moderating variables at the Tax Service Office (KPP) Pratama Denpasar Barat. The method of this research is Moderated Regression Analysis (MRA). The research results show that understanding tax regulations and the role of tax consultants has a positive effect on taxpayer compliance, while taxpayer awareness and tax sanctions have a negative effect on taxpayer compliance. Furthermore, risk preference as a moderating variable is able to weaken the influence of understanding tax regulations, taxpayer awareness, tax sanctions, and the role of tax consultants on taxpayer compliance. The conclusion of this research shows that factors from taxpayers have an important role in increasing taxpayer compliance, especially at the KPP Pratama Denpasar Barat. The advice that can be given from this research is for practitioners to carry out regular outreach both offline and online regarding the importance of taxes and show transparency in the use of taxes so that mutual trust and awareness arise between the government and society.